Development and performance of tetraploid hybrids of plantain (Musa spp., AAB group) with black sigatoka resistance - Vuylsteke, D.R.; Swennen, Rony L. (1994)
A strategy to control the black sigatoka disease of plantain (Musa spp, AAB group) in Africa, targeting the incorporation of durable host plant resistance, was initiated at the International Institute of Tropical Agriculture (IITA). The commonly accepted intractability of plantain to genetic improvement has been challenged by the identification of 37 different, seed-fertile plantain cultivars and by the production of 250 hybrids in four years of breeding. Twenty tetraploid hybrids have been selected for their increased black sigatoka resistance, high yields, large parthenocarpic fruits and better rationing. Seventeen of the selected hybrids had 'Calcutta 4' (Musa acuminate spp. Burmannicoides AA group) as male parent, which indicates that the inferior bunch characteristics of this wild banana were not necessarily transmitted to tetraploid progeny. Conversely, the black sigatoka resistance of 'Calcutta 4' was readily inherited in the tetraploid off-spring. Progenies of the triploid French plantain cultivars 'Obino l'Ewai' and 'Bobby Tannap' differed in their breeding values, the former producing larger numbers of promising hybrids. Tetraploids produced from crosses of a plantain cultivar with the homozygous 'Calcutta 4' displayed variation in qualitative traits and growth and yield parameters, suggesting the occurrence of recombination in the triploid plantain genome during megasporogenesis, even when there is restitution of the full triploid genome.